The Influence of Training and Mentoring on Rice Farmers’ Productivity in Supporting Food Security in Rambah Muda Village - Tio Wahyu Nugroho; Arfianti Novita Anwar; Makmur Makmur (International Journal of Economic and Tourism Research, 2026)
The agricultural sector plays an essential role in supporting food security and improving rural community welfare in Indonesia. However, agricultural productivity in many rural areas remains relatively low due to limited human resource capacity, inadequate adoption of agricultural technology, and insufficient technical guidance for farmers. This study aims to analyze the influence of training and mentoring on the productivity of rice farmers in Rambah Muda Village, Rambah Hilir District, Rokan Hulu Regency. The research employed a quantitative approach with a causal associative design. The population consisted of 120 farmers, while the sample comprised 50 respondents determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires using a Likert scale and supported by observation and informal interviews. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that training has a positive and significant effect on farmers’ productivity (t = 4.742; p < 0.05), while mentoring also has a positive and significant effect (t = 2.579; p < 0.05). Simultaneously, training and mentoring significantly influence farmers’ productivity (F = 29.874; p < 0.05). The coefficient of determination indicates that 82.9% of farmers’ productivity can be explained by the variables of training and mentoring. These findings suggest that capacity-building programs through structured training and continuous mentoring play a strategic role in improving farmers’ productivity and supporting sustainable food security at the local level (Dessler, 2020; Mardikanto, 2018; FAO, 2021). Therefore, agricultural development policies should emphasize integrated farmer empowerment programs that combine knowledge transfer with field-based mentoring to enhance agricultural productivity and rural welfare.